IMPLEMENTASI REDD+ DI TAMAN NASIONAL MERU BETIRI DENGAN DUKUNGAN BUDIDAYA JAMUR TIRAM OLEH MASYARAKAT - Ari Wibowo,M.Sc (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2018)
In the context of climate change, program for reducing emissions from deforestation and degradation (REDD+) are in line with forest conservation efforts. However, efforts in forest conservation, including those in conservation area of Meru Betiri National Park (MBNP) encountered various disturbances that can threaten sustainability. The existence of community in surrounding areas of MBNP can be a threat, mainly due to illegal logging and forest encroachment caused by lack of awareness and economic problems. One important effort to protect forest areas is empowerment of communities to participate in forest conservation as well as to provide benefits, especially economic benefits. In the implementation of demonstration activities of DA REDD+, one of the activities facilitated by the program was development of oyster mushroom cultivation by communities around MBNP. Research by collecting field information related to the implementation of DA REDD+ in MBNP provided information on the implementation of DA REDD+ activities, social and economic aspects of communities and the results of SWOT analysis of the activities of oyster mushroom cultivation around the MBNP. This activity was to support the implementation of REDD+ program and to support forest conservation efforts through improvement of community income that also can be applied in other protected areas.